Konsep Dasar Ekonomi Internasional dan Teori Perdagangan Internasional - Aulia, Rachel Deska; Putri, Intan Rizkia; Arianthony, Syahron (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article discusses the fundamental concepts of international economics and international trade theories as a foundation for understanding economic relations between countries. The core issue addressed is how international economic theories can explain the benefits and challenges of global trade. This study employs a descriptive qualitative approach through literature review from various credible sources. Findings reveal that international economics plays a crucial role in expanding markets, enhancing production efficiency through specialization, and fostering economic growth through trade, investment, and technology exchange. Key theories such as Absolute Advantage by Adam Smith, Comparative Advantage by David Ricardo, and modern theories like the Heckscher-Ohlin model and Paul Krugman’s New Trade Theory are presented to understand the increasingly complex trade dynamics. On the other hand, protectionist policies, non-tariff barriers, and economic disparities between countries pose significant challenges in global trade. The study concludes that a comprehensive understanding of international economics is essential for countries to formulate adaptive and strategic trade policies, enabling them to compete effectively and gain optimal benefits from economic globalization. The article also recommends further research to evaluate the impact of international trade on specific sectors, such as SMEs, to support the formulation of more inclusive and sustainable economic strategies.